Anesthetic Management During Pediatric Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy With Cisplatin in a Small Child: A Case Report and Systematic Literature Review. Issue 1 (1st January 2020) - Zajonz, Thomas S.; Padberg, Winfried; Mann, Sacha T. W.; Gehron, Johannes; Sander, Michael; Mann, Valesco
Abstract : Cytoreductive surgery (CS) and hyperthermic intraperitoneal chemotherapy (HIPEC) present a challenging task for anesthesia providers. Anesthesia management may be complicated by hyperthermia, fluid shifts, and distinct inflammatory response. Only a few reports dealing with the anesthesia management of pediatric CS and HIPEC have been published. We report a case of a 2-year-old child with a relapse of an alveolar rhabdomyosarcoma of the uterus and peritoneal carcinomatosis treated with CS and HIPEC. For children, careful temperature measurement, intraoperative prevention of hyperthermia, and sufficient volume management are important, as well as postoperative pediatric intensive care with experience CS and HIPEC patients.